(untitled) (CIPEEX, 2026)
Introduction: Chikungunya fever, caused by the Chikungunya virus (CHIKV) and transmitted by Aedes aegypti, represents a significant public health problem in Brazil. After the first autochthonous cases in 2014, the disease has been expanding in several regions, including Goiás. In Anápolis, understanding the epidemiological evolution of the infection is essential to inform prevention strategies. Objective: To analyze the epidemiological aspects of Chikungunya fever in Anápolis, Goiás, over the last five years, identifying its sociodemographic profile, temporal distribution, and clinical manifestations. Method: This is an observational, ecological study conducted with secondary data from SINAN and the Municipal Health Department, covering the period 2020 to 2024. Variables such as sex, age group, reported symptoms, and spatial distribution were assessed. Results: During this period, 170 cases were confirmed. The incidence was low in 2020 and 2021 (2 cases each year), but increased significantly from 2022 onwards, peaking in 2023 (46.4% of reports). Females predominated (59.4%), and the most affected age group was 20 to 44 years (44.7%). The most common symptoms were fever and myalgia (84.7%), headache (70.6%), and arthralgia (64.7%). Conclusion: The analysis revealed a significant increase in Chikungunya in Anápolis, especially after the COVID-19 pandemic. The identified profile points to a greater impact on women and economically active adults. The results highlight the importance of strengthening epidemiological surveillance and vector control measures to reduce the incidence and impact of the disease.